PENGARUH RETURN ON INVESTMENT, DEBT TO EQUITY RATIO, ECONOMIC VALUE ADDED, INFLASI TERHADAP RETURN SAHAM PADA TAHUN 2008-2012 - Ayu Nisaa Harvioni; Astohar Astohar (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2016)
This study aimed to analyze the influence of Return On Investment,Debt To Equity Ratio, Economic Value Added, and Inflation on StockReturns. This study was made as there are differences between the results ofresearch with each other and so can be used to predict fluctuations stockreturns.Sample of this research is 135 others company in IDX with methodpurposive sampling.This study uses multiple linear regression statistic to testthe hypothesis. The variable used in this study Return On Investment, DebtTo Equity Ratio, Economic Value Added, Inflation, and Stock Returns. Typeof data used in the form of secondary data is data such as notes and reportstaken from Indonesian Capital Market Directory.The results showed that simultan independent variables effect on stockreturn. While research is partially showed Return On Investment positive andnot significant effect on stock returns. While Debt To Equity Ratio negativeand significant effect on stock returns. Meanwhile Economic Value Addedpositive and significant effect on stock returns. And then inflation negativeand not significant effect on stock returns. In addition it was found that thevalue of adjusted R square is 5,8%. This means that 5,8% of the movement ofstock returns can be predicted from the four variables, while at 94,2% isexplained by other variables outside the model